Altered peripheral nerve structure and function in latent autoimmune diabetes in adults. Issue 3 (13th December 2019) - Issar, Tushar; Yan, Aimy; Kwai, Natalie C. G.; Poynten, Ann M.; Borire, Adeniyi A.; Arnold, Ria; Krishnan, Arun V.
Abstract: Aim: The present study was undertaken to investigate mechanisms of peripheral nerve dysfunction in latent autoimmune diabetes in adults (LADA). Materials and methods: Participants with LADA (n = 15) underwent median nerve ultrasonography and nerve excitability to examine axonal structure and function, in comparison to cohorts of type 1 diabetes (n = 15), type 2 diabetes (n = 23) and healthy controls (n = 26). The LADA group was matched for diabetes duration, glycaemic control, and neuropathy severity with the type 1 and type 2 diabetes groups. A validated mathematical model of the human axon was utilized to investigate the pathophysiological basis of nerve dysfunction. Results: The most severe changes in nerve structure and function were noted in the LADA group. The LADA cohort demonstrated a significant increase in nerve cross‐sectional area compared to type 1 participants and controls. Compared to type 1 and 2 diabetes, measures of threshold electrotonus, which assesses nodal and internodal conductances, were significantly worse in LADA in response to both depolarising currents and hyperpolarising currents. In the recovery cycle, participants with LADA had a significant increase in the relative refractory period. Mathematical modelling of excitability recordings indicated the basis of nerve dysfunction in LADA was different to type 1 and 2 diabetes. Conclusions: Participants with LADA exhibited more severe changes in nerve function and different underlying pathophysiological mechanisms compared to participants with type 1 or 2 diabetes. Intensive management of risk factors to delay the progression of neuropathy in LADA may be required.